The Influence of User Factors on AI and User Experience in the Lazada - Dinda Virgia Yurendira; Brilian Dwi Saputra; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research reviews specific problems in considering how much influence the factors of user data security, user satisfaction, user retention, application of artificial intelligence (AI) and impact on user experience. The goal is to provide useful guidance for app developers and e-commerce business owners to improve User Experience and integrate AI effectively. This research is included in Quantitative study by distribute questionnaires online to Lazada application users. The aim is to understand user views of Lazada application services. And these factors have a significant role in maintaining competitiveness and improving applications. And the research concludes that user data security and user retention factors have worthy of attention on applications of artificial intelligence and user experience. However, user experience with the application of artificial intelligence (AI) and user experience have an insignificant influence.